PENERAPAN METODE FUZZY LOGIC UNTUK SISTEM PAKAR MENDIAGNOSA PENYAKIT ALERGI PADA ANAK - Rahayu, Sri Lestari (Lembaga Penelitian Dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2016)
Indonesia is one country that has a very large number of people in the world . The population is very big cause various problems , such as uneven economic development and education, especially in remote areas , it is resulting in the emergence of health problems.Health is very important to note for the development of a better country. By having a healthy young generation, will produce a successor to a strong and able to compete without hampered by limitations. Until now, if a child has a variety of disorders do not realize that the disorder is apparently caused by food allergies. Various such disorders often incorrectly perceived by society and even by some doctors. Often mistaken for a variety of disorders of the other things that food allergy sufferers often experience overdiagnosis and overtreatment other diseases. Allergies can be defined as an exaggerated reaction of the immune system as a response to bodily contact with foreign objects from the outside. The method used in diagnosing allergic disease in children is Fuzzy Logic, the programming language used is PHP and Software used are Dreamweaver. The purpose of this study is to facilitate the user in diagnosing allergic disease in children based on symptoms entered by the user.